Struktur Komunitas Mangrove Di Distrik Klaurung Kelurahan Klablim Kota Sorong - Elvira Howay; Roger Tabalessy; Dwi Indah Widya Yanti; Joelan Palemba; Clara Payung (INTEGRATED OF FISHERIES SCIENCE, 2023)
As a typical ecosystem for coastal areas, mangrove ecosystems have many functions and benefits in supporting the sustainability of other ecosystems involved in it. Mangrove forests play an important role in stabilizing coastlines and helping to reduce the impact of natural disasters such as tsunamis and hurricanes. This study aims to determine the extent of mangrove cover in Klablim Vilage, Klaurung District. The method used in this research is line transect, which is carried out by making a perpendicular line to the land by making maps or plots. One of the advantages of using this method is that it is more efficient. This method is faster, requires less equipment, and requires fewer observers. The results of this study found the diversity of mangrove species in Klablim Village, Klaurung District, consisting of Rhizophora sp, Xylocarpus sp, Bruguier asp and Soneratia sp. The relative frequency of mangroves found in Klablim Village, Klaurung District, is Rhizophora sp 62.5%, Xylocarpus sp 12.5%, Bruguiera sp 12.5% ​​as well as Soneratia sp 12.5%. The relative density of mangroves found in Klablim Village, Klaurung District, for the species Rhizophora sp 68%, Xylocarpus sp 16%, Bruguierasp 8% and Soneratia sp 8%. The relative cover for Rhizophora sp species was 92.3%, Xylocarpus sp 5.11% species, Bruguiera sp 1.27% and Soneratia sp 1.27%.